Fluoride intake from drinking water and dentifrice by children living in a tropical area of Brazil Ingestão de flúor pela água e creme dental por crianças residentes de uma área de clima tropical do Brasil - Leila Maria F. Omena; Milton F. de A. Silva; Cleone Calheiros Pinheiro; Jairo C. Cavalcante; Fábio Correia Sampaio (University of São Paulo, 2006)
OBJECTIVE: To assess fluoride (F-) intake from water and toothpaste by children aged 18 to 36 months and to monitor the F- concentrations in the drinking water system in a tropical city of Brazil. METHODS: Children (n=58) aged 18-36 months, all lifetime residents of Penedo, state of Alagoas, Brazil, participated in this study. Water F- analyses were carried out in 7 different occasions at least a week apart. For 2 days all the water drunk by each child was accounted for. Fluoride intake from water for each child was estimated using the mean F- concentration of water in 7 different occasions. Fluoride intake from toothpaste was estimated by subtracting the recovered post-brushing F- from the original amount placed in the toothbrush. The F- intake from water and toothpaste was estimated by dividing the total amount of F- ingested by the weight of each child. RESULTS: The mean F- concentration in the drinking water was 0.94 ppm (mean range 0.78-1.1 ppm), which is above the 0.7 ppm recommended for this area of Brazil. Mean total F- intake from water and toothpaste was 0.128 mg F-/Kg Body Weight/day. The daily means of F- intake from water and toothpaste were 0.021 and 0.107 mg F-/Kg Body Weight, respectively. Ninety six percent of children showed F- intake above 0.07 mg F-/Kg Body Weight/day. CONCLUSIONS: Children in Penedo are at risk for developing dental fluorosis due to high F- intake from fluoridated toothpastes. Water fluoridation showed low contribution to the total F- intake. However, high water F- concentrations in the water indicate the need of surveillance of the artificial water fluoridation system. OBJETIVOS: determinar a ingestão de flúor (F-) pela água e creme dental em crianças de 18 a 36 meses de idade que moram em uma cidade de clima tropical no Brasil e monitorar as concentrações de F- no sistema de água potável. MATERIAIS MÉTODOS: participaram deste estudo crianças (n=58), 18-36 meses, todas residentes vitalícias de Penedo (Alagoas), Brasil. As análises de F- em amostras de água foram realizadas em 7 ocasiões diferentes em semanas separadas. Durante 2 dias toda a água bebida por cada criança foi considerada. A ingestão de fluoreto para cada criança foi calculada pela média de flúor na água nas 7 ocasiões diferentes. A ingestão de F- pelo creme dental foi calculada subtraindo a saliva recuperada do expectorado pela quantidade de F- colocada na escova dental. A ingestão de F- de água e pasta de dentes foi calculada dividindo a quantia de F ingerida pelo peso de cada criança. RESULTADOS: A concentração média de F- em água potável foi de 0,94 ppm (variando de 0.78-1.12 ppm) estando acima do recomendado para esta área do Brasil que é de 0,7 ppm. A ingestão de F- total (água + creme dental) foi de 0,128 mg de F/Kg peso/dia. As médias diárias de ingestão de F- pela água e creme dental foram de 0,021 e 0,107 mg F-/Kg de peso corporal dia, respectivamente. Noventa que seis por cento das crianças demonstraram ingestão de F- superior a 0,07 mg de F-/Kg peso/dia. CONCLUSÕES: crianças em Penedo estão sob risco de desenvolver fluorose dental devido a elevada ingestão de F- pelo creme dental fluoretado. Adição de flúor à água de água mostrou baixa contribuição ao flúor total ingerido. Porém, altas concentrações de F- na água indicam a necessidade de vigilância do sistema de fluoretação artificial das águas.